Sintesis Biodiesel Dari Minyak Nyamplung (Calophyllum Inophyllum L.) Menggunakan Katalis Lantanum/Lempung; Pengaruh Variasi Logam Lantanum Dan Rasio Mol Minyak : Metanol - Ibnu Oktariza; Syaiful Bahri; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Biodiesel can be made from Alexandrian laurel oil as one of alternative energy replacement for fossil fuels. This aims of this research were determine the effect of lanthanum metal variation and variation in the ratio of oil : methanol against product results biodiesel, to produce biodiesel from Alexandrian laurel oil as alternative fuels renewable energies that can be renewed and identify the characteristics of the physical and chemical properties of biodiesel produced. Catalyst is made by grinding the clay to a size of -100 +200 mesh, then clay was activated using H2SO4 solution 1.2 M. The variation of lanthanum metal impregnation on clay are 0%-b, 1%-b, 3%-b, 5%-b, then calcined, oxidation and reduction. Production of biodiesel is carried out through two stage: esterification and trans-esterification with variation in the mole ratio of oil : methanol is 1 : 6, 1 : 9 and 1 : 12. Alexandrian laurel oil sample weight 50 gram and 3% by weight of catalyst added to the to trans-esterification reactor. The reaction lasted at 60 0C with agitation speed 400 rpm for 120 minutes. This research resulted in the largest biodiesel yield on the use of La(1%)/clay catalyst with variation mole ratio of oil : methanol 1 : 9 is 86.90%. The characteristics of the catalyst that has a surface area ratio respectively 2.95, 40.22, 27.59, and 18.48 (m2/g). The Biodiesel produced in accordance with established standards (SNI 04-7128-2016).Keywords : biodiesel, Alexandrian laurel oil, lanthanum/clay catalyst